(3GdCdajI GdhQOjIs - (3YeQ Hf eXaQ Hf YeQ H eMeO GHf CHj GdahGQS, CHh MaU, Rjf GdOjf GHf GdhQOj GdeYQj GdcfOj,J (B749 (3g` s ((3GdfLa s)
(3ChdgG (B:s
(3hHYO aGdJYHjQ Yde MSf haVdg ai jhSa eHjf s
(3BNQgG (B:s
(3hGLYd eMeO fHi PNQi ai gPg GdOfjG hjhe MTQi s
(3HChdg agQSJ ddeNWhWs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B228 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B3s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B157s
Keywords: (3JYHjQ GdQDjGs